Optimal illusions and decisions under risk - Christian Gollier (Center for Economic Studies and ifo Institute (CESifo), 2005)
We examine a static one-risk-free-one-risky asset portfolio choice when the investor's wellbeing is affected by the anticipatory feelings associated to potential capital gains and losses. These feelings can be manipulated by the choice of subjective beliefs on the distribution of returns. However, the bias of these endogenous subjective beliefs induces the choice of a portfolio that is suboptimal with respect to the objective expected utility of final wealth. We characterize the structure of these optimal beliefs. We first show that optimal subjective beliefs must be degenerated with only two possible returns. Moreover, under some weak conditions on the utility function, these two atoms are at the lower and upper bounds of the objectively feasible returns. When the intensity of anticipatory feelings is small, the formation of beliefs must be biased in favor of optimism, which implies an increase in the equilibrium demand for the risky asset. We also show that the optimal beliefs are approximately independent of the investor's degree of risk aversion.
Keywords: D81; 330; anticipatory feelings; portfolio choice; overconfidence; positive thinking; endogenous beliefs; Anlageverhalten; Portfolio-Management; Emotion; Erwartungstheorie; Scheingewinn; Bias; Theorie